Content Analysis of Sarcasm in Warintil Episode 186 (July 1 2020) - Puput Pitria Ulandari; Sapta Sari; Indria Indria (Penerbit Jurnal Indonesia, 2022)
Sarcasm is a figure of speech derived from irony and is harsher than irony. The main characteristic of sarcasm is that it always contains bitterness and reproach that is bitter, hurts the heart, and is not pleasant to hear. Through the film Warintil episode 186, the media was able to display a picture of the sarcasm that was uttered by the players. This study aims to describe the forms of sarcasm in the film Warintil episode 186. The method used in this research is descriptive qualitative using content analysis method. The data obtained for this analysis is obtained through several scenes in which there is an element of sarcasm. Then after choosing what sarcasm language is in the film, then determine what type of sarcasm is in the film. While the theory used is the content analysis theory of Holsti. The results showed that in the Warintil episode 186 film, there were 13 sarcasm quotes in the Warintil episode 186 film that fulfilled the unit of analysis where each sarcasm was shown in scenes 3:15 to 8:32. In the film Warintil episode 186, there are thirteen quotes that have the meaning of insulting/insulting.